2011
DOI: 10.1016/j.curtheres.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2 Different Doses of Pregabalin on Morphine Consumption and Pain After Abdominal Hysterectomy: A Randomized, Double-Blind Clinical Trial

Abstract: Pregabalin at a total dose of 600 mg, administered before operation and at 12 hours postoperatively after abdominal hysterectomy, reduced morphine consumption and pain intensity and increased patient satisfaction. No significant differences in side effects were observed between the study groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
5
28
0
1
Order By: Relevance
“…induced hyperalgesia and opioid consumption in patients 43,44 through a largely unknown mechanism. Although the therapeutic action of gabapentinoids, including gabapentin and pregabalin, is mediated by α2δ-1 binding, 23,26,35 gabapentinoids have no effect on the interaction between α2δ-1 and voltage-gated Ca 2+ channel α1 subunits or voltage-gated Ca 2+ channel activity in neurons and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…induced hyperalgesia and opioid consumption in patients 43,44 through a largely unknown mechanism. Although the therapeutic action of gabapentinoids, including gabapentin and pregabalin, is mediated by α2δ-1 binding, 23,26,35 gabapentinoids have no effect on the interaction between α2δ-1 and voltage-gated Ca 2+ channel α1 subunits or voltage-gated Ca 2+ channel activity in neurons and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…0.71 [-1.18, -0.23] Heterogeneity: Tau 2 = 0.17; Chi 2 = 10.61, df = 6 (P = 0.10); I 2 = 43% Test for overall effect: Z = 2.91 (P = 0.004) Heterogeneity: Tau 2 = 0.52; Chi 2 = 105.20, df = 18 (P < 0.00001); I 2 = 83% Test for overall effect: Z = 4.16 (P < 0.0001) Heterogeneity: Tau 2 = 0.74; Chi 2 = 163.74, df = 14 (P < 0.00001); I 2 = 91% Test for overall effect: Z = 3.25 (P = 0.001) Heterogeneity: Tau 2 = 0.65; Chi 2 = 321.89, df = 40 (P < 0.00001); I 2 = 88% Test for subgroup differences: Chi 2 = 0.11, df = 2 (P = 0.95); I 2 = 0% Test for overall effect: Z = 5. 51 Test for overall effect: Z = 1.28 (P = 0.20) Heterogeneity: Tau 2 = 0.29; Chi 2 = 94.68, df = 22 (P < 0.00001); I 2 = 77% Test for overall effect: Z = 3.14 (P = 0.002) Heterogeneity: Tau 2 = 0.28; Chi 2 = 66.36, df = 14 (P < 0.00001); I 2 = 79% Test for overall effect: Z = 2.02 (P = 0.04) . VAS pain scores at 3 months at rest were investigated in three studies 7 9 13 and during movement in two studies 7 9 with no statistically significant differences between the groups.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…51 57 studies. Pooled results showed a statistically significant reduction in pain scores at rest [MD (95% CI)¼ 20.81 (21.07, 20.51, I 2 ¼88%)] and during movement [MD (95% CI)¼ 20.58 (20.94, 20.21, I 2…”
mentioning
confidence: 99%
“…A group of studies done on patients who underwent hysterectomy like that done by Ittichaikulthol et al [16] , Yücel et al [17] and Fassoulaki et al [18] as well as many studies done in 2014 like that of Chotton et al [19] , Eman et al [20] and George et al [21] . All these studies had found a significant post-operative reduction in VAS-100 score in patients who took different dose regimens of oral pregabalin (75-150 mg) in comparison with those who took any post-operative NSAID analgesic or placebo, which went in accordance with the current study.…”
Section: Discussionmentioning
confidence: 99%